Exploring the teaching and learning of accounting: a case of a South African university - Moyo, Grate Ndabezihle (University of the Free State, 2023)
The aim of this paper was to determine the accounting lecturers’ teaching practices at a South African higher education institution. Teaching practices are a complex set of ways which lecturers use for instruction. When compromisingly crafted and implemented, the impact is on students’ success. Hence the application of lecturers’ minds is needed in the process. In accounting education, teaching practices were found cognitively driven to determine success. Hence cognitivism learning theory guided this study. Cognitivists, and accounting educationists believe in related key elements; mental processes, thinking, remembering, solving complex problems, focussing on tasks requiring an increased level of information processing, classification, and procedural rules. Related key elements enhance the crafting of accounting teaching practices. This paper used a qualitative exploratory research methodology which enabled the researcher engaging to engage with participants in their natural settings. Three first first-year accounting lecturers were purposefully selected for this study. Data was generated through Microsoft teams Teams interviews determining different practices used in teaching accounting. Furthermore, responses from participants were used to corroborate the data generated. Issues such as participants’ teaching practices, knowledge of feedback teaching practices, and challenges experienced by accounting lecturers were explored. Data was analysed through thematic analysis. The Finally, the paper responded to one question: what are the teaching practices used by accounting lecturers? Findings suggest that some of the current accounting teaching practices are a detriment to the undesirable performance, which cannot be ignored. Additionally, there is no consistency in the application of accounting teaching practices, yet more research specifically in accounting education is needed to enhance performance. Hence this paper further suggests that university accounting teaching practices require intervention to encourage effectiveness.
Dissertation (M.Ed.(Higher Education Studies))--University of the Free State, 2023
Keywords: Accounting; Teaching; Teaching practices; Cognitivism; Lecturers; Education